Preparação e caracterização de pontos de carbono e material carbonoso nanoestruturado a partir da celulose e nanocristais de celulose - Debora Rosa da Silva Souza (2017)
Cellulose is a naturally occurring polymer, which is the main constituent of biomass. Various carbon structures can be prepared from biomass, generating materials on a micro or nanometric scale. In this work, eucalyptus cellulose fibers and cellulose nanocrystals (NCC) produced from the same source were used as precursors for the process of obtaining carbonaceous material through different methods, involving pyrolysis, microwave assisted hydrothermal carbonization and carbonization through acid dehydration and oxidation. The prepared materials were characterized for their structural, morphological and optical properties. In general, the pyrolysis of cellulose and CNC allowed the formation of leaf shape structures, rode-shape and spherical structures with different sizes, in addition to the formation of carbon dots (CD), when the precursor used was the CNC. CD were also obtained by the microwave assisted hydrothermal carbonization of CNC, obtaining almost spherical nanometric structures with a diameter of between 1.7 and 4.6 nm and fluorescence, such as emission in the region between 400-500 nm, depending on the wavelength of excitation.The methodology of carbonization by acid dehydration and oxidation (CADO) was very efficient to obtain CD with a homogeneous dispersion size, with an average diameteraround 2.35nm.Typical emissive carbon dots behaviors were observed for the samples produced in this work, which showed dependence between excitation wavelength and fluorescence, and emissions in the blue region of the visible spectrum. Several characterization techniques were used, including FTIR, MET, UV-vis spectroscopy, fluorescence spectroscopy, thermal analysis, among others. The carbon dots have a highly functionalized surface, with many oxygen groups (carboxylic, carbonylic, phenolic, etc.), which allowed to perform surface modification reactions. Carbon dots obtained via CADO were submitted to surface passivation with tetraethylenepentamine (TEPA) and PEG1500N, in addition to surface modification with hydrazine hydrate. The properties of the carbon dots were evaluated after passivation.